Inovasi Pelayanan “Lek Paijo” Di Bapenda Kota Semarang - Wardah Meliana Sihab; Hesti Lestari; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2022)
The success of local governments, in increasing local indigenous income, can be achieved through excellent service, which is provided to the community. The implementation of Lek Paijo service innovation at the Semarang City Regional Revenue Agency is expected to increase local revenue. This research was carried out in order to determine the characteristics of service innovations for the Regional Tax Electronic Service Online Network System (Lek Paijo) in Bapenda Semarang City and analyze the inhibiting factors and drivers of service innovation. This type of research is qualitative research with data collection methods through interviews, observations and documentation. This research uses the theory of innovation characteristics, to be able to find out the driving factors and obstacles to the implementation of innovation. The results of this study, namely the Innovation of Regional Tax Electronic Services Online Network System (Lek Paijo) can answer problems in public services, but in its implementation there are still problems including. Driving factors: infrastructure provided is technology-based, there is cooperation with stakeholders, the ability of human resources in the organization. The inhibiting factors are: the socialization carried out has not been evenly distributed, there is no maintenance or maintenance of innovative tools or machines and the units provided are minimal or limited, as well as the behavior or mindset of people who prefer to pay their obligations at any time they are due. Suggestions that can be given by researchers are to place paid advertisements, add machines or innovation tools, carry out periodic maintenance or maintenance on innovation machines or tools, provide warning messages to the public.